Early, integrated palliative rehabilitation improves quality of life of patients with newly diagnosed advanced cancer: The Pal-Rehab randomized controlled trial. (July 2021) - Nottelmann, Lise; Groenvold, Mogens; Vejlgaard, Tove Bahn; Petersen, Morten Aagaard; Jensen, Lars Henrik
Background: Early integration of palliative care into oncology treatment is widely recommended. Palliative rehabilitation has been suggested as a paradigm which integrates enablement, self-management, and self-care into the holistic model of palliative care. Aim: We hypothesized that early integration of palliative rehabilitation could improve quality of life. Design: The Pal-Rehab study (ClinicalTrials.gov NCT02332317) was a randomized controlled trial. The 12-week intervention offered by a specialized palliative care team was two mandatory consultations and the opportunity of participating in an interdisciplinary group program. Supplementary individual consultations were offered, if needed. Setting/participants: At Vejle University Hospital, Denmark, adults diagnosed with advanced cancer within the last 8 weeks were randomized 1:1 to standard oncology care or standard care plus intervention. Assessments at baseline and after six and 12 weeks were based on the European Organization for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30). At baseline participants were asked to choose a "primary problem" from a list of QLQ-C30 domains. The primary endpoint was the change in that "primary problem" measured as area under the curve across 12 weeks ( T -scores, European mean value = 50, SD = 10). Results: In all, 288 were randomized of whom 279 were included in the modified intention-to-treat analysis (146 in the standard care group and 133 in the intervention group). The between-group difference for the primary outcome was 3.0 (95% CI [0.0–6.0]; p = 0.047) favoring the intervention. Conclusion: Early integration of palliative rehabilitation into standard oncology treatment improved quality of life for newly diagnosed advanced cancer patients. Trial registration: Clinicaltrials.gov Identifier: NCT02332317, registered on December 30, 2014.